2015
DOI: 10.1007/s00431-015-2615-4
|View full text |Cite
|
Sign up to set email alerts
|

Medicine preparation errors in ten Spanish neonatal intensive care units

Abstract: Calculation errors are avoided using concentration standard preparation protocols. Accuracy in the preparation process depends mainly on the degree to which commercial drug preparations meet current legal requirements and the syringes and preparation techniques used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 25 publications
1
35
0
6
Order By: Relevance
“…Therefore, our findings need to be confirmed in multiple hospital settings, to enable generalization, and more studies of IPISs are needed. In most countries where IV preparation errors were reported, ready-to-use IV bags, eMARs, and smart pumps with bar codes are not in common use yet [12,13,[22][23][24][25][48][49][50][51][52][53][54]. However, these systems will likely be implemented in the future.…”
Section: Study Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our findings need to be confirmed in multiple hospital settings, to enable generalization, and more studies of IPISs are needed. In most countries where IV preparation errors were reported, ready-to-use IV bags, eMARs, and smart pumps with bar codes are not in common use yet [12,13,[22][23][24][25][48][49][50][51][52][53][54]. However, these systems will likely be implemented in the future.…”
Section: Study Limitationmentioning
confidence: 99%
“…The verification of appropriate solution for IV admixture and preparation of IV drugs by centralized IV admixture services in pharmacy departments ensure the safety and stability of IV drugs and contribute to the quality use of IV antimicrobials [21,22]. However, for a hospital that is unable to adopt the centralized preparation of IV drugs because of a lack of pharmacists, information systems such as the IPIS used in this study could be a strategy for improving IV preparations [12,13,[22][23][24][25]. We found that implementing the IPIS in the setting of our study encouraged medical doctors to specify the reconstitution solution clearly, and the PRR increased over several months.…”
mentioning
confidence: 99%
“…As a recent illustration, we refer to the evaluation of the use of uncoated mini-tablets instead of syrup for neonates. Uncoated mini-tablets offer the potential of a single formulation for different age groups and [5,6,10,11,13,15], and pharmacovigilance [7,8] in neonates, but should also shift towards medicines and product development driven by neonatal pathophysiology [9] avoid the need for specific excipients or taste-masking compounds [10,15].…”
Section: Neonatal Clinical Pharmacy: How To Cope With Neonatal Formulmentioning
confidence: 99%
“…The study group hereby evaluated the impact of a structured intervention (protocol standardization, education) on the number of errors and documented significant improvements in both calculation errors (1.35 to 0 %) and accuracy (54.7 and 38.3 % to 38.3 and 14.6 % in NICU and HP, respectively) [6]. This intervention paper follows on a previous paper which described a pre-intervention phase [5] and illustrates the potential impact of preventive strategies on the extent of drug errors.Development of a roadmap to improve neonatal pharmaceutical care should aim to improve the knowledge on clinical pharmacology, clinical pharmacy, and approaches to improve the knowledge and use of neonatal pharmacovigilance initiatives [1]. Another keystone component of such a roadmap should focus on neonatal drug development, i.e., drug development driven by neonatal pathophysiology (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation